Grammar instruction in the Malaysian ESL classroom: a case study / Zainon Abu Bakar - Abu Bakar, Zainon (2010)
With a renewed interest to look at grammar instruction in the Malaysian ESL classroom, linguists and language researchers are re-exploring the explicit-implicit dimension of grammar instruction. Therefore it was felt that in such a situation it would be pertinent to explore both students’ and teachers’ perspectives on grammar instruction and this was the main aim of the study. This descriptive case study explored both students’ and teachers’ perceptions with regards to aspects such as student motivation, their attitudes and their beliefs on grammar instruction in their ESL classrooms. The study was conducted in a boarding junior college, Maktab Rendah Sains MARA (MRSM) located in Pahang. The sample involved 203 Form Four students and 8 TESL teachers teaching at the upper secondary level. Data was collected using two questionnaires (Student Questionnaire and Teacher Questionnaire) and semi structured interviews. The interviews were conducted with twenty randomly selected students from ten Form Four ESL classes and all eight TESL teachers in this junior college. The findings of the study indicated that these Form Four students were both instrumentally and integratively motivated to learn grammar in order to improve their language proficiency. Besides, both students and teachers displayed positive attitudes towards grammar instruction in the ESL classroom and they also held strong beliefs about it. However, there existed a mismatch between the students’ and the teachers’ attitudes towards explicit and implicit approaches of grammar instruction, and their beliefs about them. This was evidenced by the students’ more positive attitudes and their stronger beliefs than that of their teachers’. In addition, a very significant difference between their views was revealed in students’ stronger belief that English class should focus on communication, not grammar. This study indicated hat both students and teachers come to the language classroom with their own attitudes, beliefs system and expectations, and therefore it is important for teachers to eliminate any incongruence that might occur and look for strategies to enhance student learning. Finally, it is recommended that future studies in the areas of attitude and belief related to explicit-implicit dimension of grammar instruction involve larger samples at other secondary schools throughout Malaysia and other data collection strategies like classroom observations.